Work-Related Musculoskeletal Disorders: The Role of Workplace Ergonomics and Its Effect on Non-Teaching Staff Healthy Living in Nigerian Public Universities - Akinbode, James; David, Joseph; Opeyemi, Oyelude; Akinrinlola, 'Mubo; Olu-Ogunleye, Itunu; Owoeye, Olumide (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Health status of an individual in paid employment is a function of many factors such as workplace settings, furniture, work design and tools used at work, among others. Based on this position, this study examined how work-related musculoskeletal disorders through workplace ergonomics determine non-teaching staff healthy living, and how each of the selected work-related musculoskeletal disorders caused by defective workplace ergonomics contributes to healthy living. Methods: This study was conducted among the non-teaching staff of selected public universities in south west Nigeria through quantitative approach that made use of descriptive research design with the use of structured questionnaire administered to collect data and both descriptive and inferential statistics were used to analyze data collected. Results: The study revealed that specific work-related musculoskeletal disorders caused by defective workplace ergonomics were of negative effect on non-teaching staff healthy living while others were not. Also, specific work-related musculoskeletal disorders (back pains and eyes dysfunctionality) examined against non-teaching staff healthy living were found to be detrimental to their health status while muscular pains, fracture, neck injuries, hand-arm vibration and bruises were of insignificant effect on the non-teaching staff healthy living. Conclusion: The study concludes that work-related musculoskeletal disorders through workplace ergonomics is an issue that management of universities should be mindful of to ensure staff healthy living as this is critical to job performance.